Perceived Peer Social Support dan Psychological Distress Mahasiswa Universitas Indonesia - Dewayani, Astri; Sukarlan, Augustine D.; Turnip, Sherly S. (Makara Human Behavior Studies in Asia, 2011)
This study investigated the difference of psychological distress between students of Universitas Indonesia who have and who does not have perceived peer social support. This quantitative study has been done by adapting HSCL-25 questionnaire to know psychological distress to differentiate students of Universitas Indonesia who perceived peer social support. Participants are 666 students of Universitas Indonesia obtained by random/probability sampling. There is no significant difference in psychological distress between students of Universitas Indonesia who have and who does not have perceived peer social support. It is assumed that there are many other factors that influence the psychological distress student.